Physical training modulates proinflammatory cytokines and the soluble Fas/soluble Fas ligand system in patients with chronic heart failure - Adamopoulos, S; Parissis, J; Karatzas,D.; Kroupis, C.; Georgiadis, M.; Karavolias, G; Paraskevaidis,J.; Koniavitou,K.; Coats,A.J.; Kremastinos, D.T. (J.Am.Coll.Cardiol., 2002)
OBJECTIVES: We sought to investigate the effects of physical training on circulating proinflammatory cytokines and the soluble apoptosis mediators Fas (sFas) and Fas ligand (sFasL) in patients with chronic heart failure (CHF). BACKGROUND: Recent investigations have shown an overexpression of circulating proinflammatory cytokines and soluble apoptosis mediators in patients with CHF, which may be related to their exercise intolerance and clinical deterioration. METHODS: Plasma levels of tumor necrosis factor-alpha (TNF-alpha), soluble TNF receptors I and II (sTNF-RI and sTNF-RII, respectively), interleukin-6 (IL-6), soluble IL-6 receptor (sIL-6R), sFas and sFasL were measured in 24 patients with stable CHF (New York Heart Association functional class II/III; left ventricular ejection fraction 23.2 +/- 1.3%) and in 20 normal control subjects before and after a 12-week program of physical training in a randomized, crossover design. Functional status of patients with CHF was evaluated by using a cardiorespiratory exercise test to measure peak oxygen consumption (VO2max). RESULTS: Physical training produced a significant reduction in plasma levels of TNF-alpha (7.5 +/- 1.0 pg/ml vs. 4.6 +/- 0.7 pg/ml, p < 0.001), sTNF-RI (3.3 +/- 0.2 ng/ml vs. 2.7 +/- 0.2 ng/ml, p < 0.005), sTNF-RII (2.6 +/- 0.2 ng/ml vs. 2.3 +/- 0.2 ng/ml, p = 0.06), IL-6 (8.3 +/- 1.2 pg/ml vs. 5.9 +/- 0.8 pg/ml, p < 0.005), sIL-6R (34.0 +/- 3.0 ng/ml vs. 29.2 +/- 3.0 ng/ml, p < 0.01), sFas (5.5 +/- 0.7 ng/ml vs. 4.5 +/- 0.8 ng/ml, p = 0.05) and sFasL (34.9 +/- 5.0 pg/ml vs. 25.2 +/- 4.0 pg/ml, p < 0.05), as well as a significant increase in VO2max (16.3 +/- 0.7 ml/kg per min vs. 18.7 +/- 0.8 ml/kg per min, p < 0.001). Good correlations were found between a training-induced increase in VO2max and a training-induced reduction in levels of the proinflammatory cytokine TNF-alpha (r = -0.54, p < 0.01) and the apoptosis inducer sFasL (r = -0.57, p < 0.005) in patients with CHF. In contrast, no significant difference in circulating cytokines and apoptotic markers was found with physical training in normal subjects. CONCLUSIONS: Physical training reduces plasma levels of proinflammatory cytokines and the sFas/sFasL system in patients with CHF. These immunomodulatory effects may be related to the training-induced improvement in functional status of patients with CHF
Keywords: Adult; Aged; Antigens,CD95; Blood; Chronic Disease; Cross-Over Studies; Cytokines; Exercise; Exercise Test; Exercise Tolerance; Fas Ligand Protein; Female; Greece; Heart failure; Humans; Male; Membrane Glycoproteins; Middle Aged; Oxygen consumption; physiology; physiopathology; Solubility